The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/jcb.26046
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Acute Regulatory Protein (StAR) Overexpression Reduces Inflammation and Insulin Resistance in Obese Mice

Abstract: Steroidogenic acute regulatory protein (StAR), a mitochondrial cholesterol delivery protein, plays a beneficial role in hyperlipidemia, NAFLD, and endothelial inflammation. Elevated circulating fatty acids and low grade inflammation are known as key risk factors of insulin resistance and type 2 diabetes. In the present study, C57BL/6J mice were fed with HFD and infected with recombinant adenovirus expressing StAR by tail-vein injection. Intraperitoneal glucose/insulin tolerance test was performed to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The worst hit enzymes were CYP17A1 which catalyses the synthesis of dehydroepiandrosterone (DHEA) from pregnenolone, as well as 3β‐HSD and 17β‐HSD that catalyse the downstream reactions leading to the synthesis of testosterone from DHEA. Earlier study corroborated our findings that the transcript levels of 17β‐HSD and 3β‐HSD are decreased in obese rats 66 …”
Section: Discussionsupporting
confidence: 91%
“…The worst hit enzymes were CYP17A1 which catalyses the synthesis of dehydroepiandrosterone (DHEA) from pregnenolone, as well as 3β‐HSD and 17β‐HSD that catalyse the downstream reactions leading to the synthesis of testosterone from DHEA. Earlier study corroborated our findings that the transcript levels of 17β‐HSD and 3β‐HSD are decreased in obese rats 66 …”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that genes include KCP (kielin cysteine rich BMP regulator) 116 , NOG (noggin) 117 , COL6A3 118 , BTG2 119 , RPS6 120 , KLF15 121 , KLF3 122 , ZFP36 123 , ETV5 124 , TLE3 125 , NNMT (nicotinamide N-methyltransferase) 126 , WDTC1 127 , ZFHX3 128 , SIAH2 129 , MBOAT7 130 , RUNX1T1 131 , MAPK4 132 , KLF9 133 , SELENBP1 134 , HELZ2 135 , ELK1 136 , SERTAD2 137 , CRTC3 138 , ABCB11 139 , TACR1 140 , SLC22A11 141 , PER3 142 , P2RX5 143 , MFAP5 144 , FGL1 145 , OLFM4 146 , NTN1 147 , ESR1 148 , ABCB1 149 , VAV3 150 and LAMB3 151 can be used as clinical prognostic biomarkers for obesity. Genes include STAR (steroidogenic acute regulatory protein) 152 , IL1RN 153 , AQP5 154 , EGR1 155 , SFTPD (surfactant protein D) 156 , KLF10 157 , PODXL (podocalyxin like) 158 , FOXN3 159 , IL6R 160 , PBX1 161 , APOD (apolipoprotein D) 162 , ACVR2B 163 , CD34 164 , INSR (insulin receptor) 165 , APOA5 166 , STAR (steroidogenic acute regulatory protein) 167 , PDK4 168 , GLS (glutaminase) 169 , FKBP5 170 , SLC6A15 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies found that KCP (kielin cysteine rich BMP regulator) [117], NOG (noggin) [118], COL6A3 [119], BTG2 [120], RPS6 [121], KLF15 [122], KLF3 [123], ZFP36 [124], ETV5 [125], TLE3 [126], NNMT (nicotinamide N-methyltransferase) [127], WDTC1 [128], ZFHX3 [129], SIAH2 [130], MBOAT7 [131], RUNX1T1 [132], MAPK4 [133], KLF9 [134], SELENBP1 [135], HELZ2 [136], ELK1 [137], SERTAD2 [138], CRTC3 [139], ABCB11 [140], TACR1 [141], SLC22A11 [142], PER3 [143], P2RX5 [144], MFAP5 [145], FGL1 [146], OLFM4 [147], NTN1 [148], ESR1 [149], ABCB1 [150], VAV3 [151] and LAMB3 [152] plays an important role in the occurrence and development of obesity, but these genes might be novel target for T1DM. STAR (steroidogenic acute regulatory protein) [153], IL1RN [154], AQP5 [155], EGR1 [156], SFTPD (surfactant protein D) [157], KLF10 [158], PODXL (podocalyxin like) [159], FOXN3 [160], IL6R [161], PBX1 [162], APOD (apolipoprotein D) [163], ACVR2B [164], CD34 [165], INSR (insulin receptor) [166], APOA5 [167], STAR (steroidogenic acute regulatory protein) [168], PDK4 [169], GLS (glutaminase) [170], FKBP5 [171], SLC6A15 [172], MT2A [173], SLC38A4 [174], AQP7 [175], ABHD15 [176], ABCA1 [177], ZNRF1 [178], PPP1R3B [179], MAOA (monoamine oxidase A) [180], UBE2E2 [181], RNASEK (ribonuclease K) [182], PREX1 [183], DGKG (diacylglycerol kinase gamma) [184], POSTN (periostin) [185], COMP (cartilage oligomeric matrix protein) [186], GAP43 […”
Section: Discussionmentioning
confidence: 99%